Los Caminos de Sefarad - Jeffrey S. Juris (Revista de Antropología Social, 2006)
This article examines the historical narratives inscribed in the material fabric of historic Jewish neighborhoods along a contemporary Jewish tourist route in Spain. Through an analysis of the guidebook, Paths of Sepharad, I explore the representation of Sephardic history and culture with respect to the growing popularity of heritage tourism and the creation of public memory. On the one hand, establishing a Jewish tourist route responds to a shift in Spanish tourism policy, which seeks to diversify the country’s tourist offerings and capitalize on the widespread infatuation with the past. Paths of Sepharad thus aims to attract a new breed of tourist –the “post-tourist”– who is motivated by a nostalgic desire for fantasy, historical voyeurism, and cultural difference. On the other hand, the commemoration of Spain’s tolerant, multicultural past and the appropriation of Sephardic heritage as its own contribu- tes to the image of Spain as a modern, pluralist democracy and helps contain potentially subversive discourses of radical “otherness”.